Partner Capabilities and Alliance Time Frame: An Analysis of International Strategic Alliances from the CEE - S. Hossein Jalali (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Partner selecton is one of the most discussed issues in strategic alliances literature. However, the majority of research has typically focused on generic partner characteristcs and presented conceptual models for alliance partner selecton, addressing clan image but only limited pieces of the partner selecton puzzle. Rooted in the resource-based view, this paper suggests that partner selecton is contngent upon the intended tme frame of strategic alliances and presents a new and intensive conceptual framework that examines the appropriate partner capability for strategic alliances, in the case of short/medium-term alliances and long-term ones. Based on empirical evidences from 736 alliances in the CEE region, the fndings stress the diﬀerences between varied partner capabilites in short/medium-term and long-term alliances. Accordingly, the signifcance of technological capability increases with the number of year’s alliances endured. Moreover, the importance of market capability decreases signifcantly when alliances last for a longer tme frame.